2005
DOI: 10.1111/j.1525-1438.2005.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of surgical treatment using laparoscopy and laparotomy in patients with endometrial cancer

Abstract: The objective of the current study was to compare the results of surgical treatment in endometrial cancer with the use of laparoscopy and the traditional approach of laparotomy. Our goal was to evaluate and compare the morbidity, recurrence rate, and disease-free survival in both groups. This article is a retrospective study. A chart review of 45 patients treated by laparoscopy between 1994 and 2002 and 136 patients treated by laparotomy between 2001 and 2002 was performed. Disease-free survival in both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Also, initially, a longer operating time should be considered. Hitherto, there have been no reports in the scientific literature describing a worse prognosis (i.e., with regard to recurrence rate, overall survival) for LAVH ± LAE compared with laparotomy ± LAE in FIGO stage I endometrial cancer [53,60]. Long-term results of large, prospective, randomized trials with sufficient statistical power are lacking though [3,18,51].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, initially, a longer operating time should be considered. Hitherto, there have been no reports in the scientific literature describing a worse prognosis (i.e., with regard to recurrence rate, overall survival) for LAVH ± LAE compared with laparotomy ± LAE in FIGO stage I endometrial cancer [53,60]. Long-term results of large, prospective, randomized trials with sufficient statistical power are lacking though [3,18,51].…”
Section: Resultsmentioning
confidence: 97%
“…In this respect, 11 studies have been identifiedone of which is a prospective, randomized trial [18,46]with no difference regarding recurrence rate and overall survival compared with the open approach being found [18,40,42,43,[47][48][49][50][51][52][53]. Chu et al [10] have reported three patients with vaginal cuff recurrence after LAVH for endometrial cancer, warning not to implement this surgical method too fast (Table 2).…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Many retrospective studies [13][14][15][16][17][18][19][20][21][22][23][24][25], prospective nonrandomized studies [26][27][28][29], and meta-analyses [49•, 50-52, 53•] published during the last decade have suggested that laparoscopic surgery has an improved outcomes profile in terms of estimated blood loss and transfusion requirements, recovery of bowel movement, postoperative hospital stay, and perioperative complications compared with laparotomy in the surgical management of endometrial cancer. These findings have been confirmed in recent RCTs comparing laparoscopy and laparotomy for surgical staging of endometrial cancer (Table 1) The following discussion of outcomes and complications of laparoscopic surgery compared with laparotomy is based on the results of the eight RCTs presented in Table 1.…”
Section: Perioperative Outcomes and Complications Of Laparoscopic Surmentioning
confidence: 99%
“…Retrospective [13][14][15][16][17][18][19][20][21][22][23][24][25] or prospective, nonrandomized studies [26][27][28][29] have shown comparable survival outcomes for laparoscopic surgery and laparotomy. Four RCTs reported the long-term survival outcomes after laparoscopic surgery compared with laparotomy in patients with endometrial cancer (Table 1) [33, 35, 36, 45••].…”
Section: Survival Outcomes After Laparoscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation